Synthesis of imidazole-pyridine derivatives as potential anti-bacterial agent / Noorshahida Ahmad Kamal - Ahmad Kamal, Noorshahida (2013)
Lately, there are many problems encounter due to the infectious diseases regarding the resistance towards anti-bacterial agents. Synthesis of new compound should be considered in order to solve these problems. Many studies and researches have been conducted which show that both imidazole and pyridine derivative show promising anti-bacterial properties. Thus, the incorporation of both compounds by synthesis is believed to produce greater anti-bacterial agent. In this study, 21 out of 26 of imidazole-pyridine derivatives have been synthesized and pure in order to study their potential anti-bacterial properties. Their chemical reactions have been monitored by using Thin Layer Chromatography (TLC) and their chemical structures have been studied by using Nuclear Magnetic Resonance (NMR). The synthesized products have shown pure which can be used for the further studies for their potential anti-bacterial activity.